(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article examines the peculiarities of Kazakh and Kyrgyz customs and traditions in family and marriage relations, as the most archaic and conservative elements of culture can be observed here. Exogamous restrictions for marriage related to social, class, ethnic and tribal affiliation of the groom and the bride, and their religion are considered.The ritual of matchmaking is described, including the customs according to which young children who had just been born were conscripted, a widow was given in marriage to the younger brother of her dead husband and a widower was married to the younger sister of his dead wife, the groom worked out a kalym in the house of his father-in-law, and the girls were abducted. The extracts concerning the matchmaking ceremony from the Kazakh lyrical poem “Kozy-Korpesh and Bayan-Sulu” and the Kyrgyz epos “Manas” are given.The wedding ceremony is also described, where numerous ritual actions were performed that go back to both ancient social marriage institutions and religious-symbolic and magical representations.